2000
DOI: 10.1093/auk/117.4.952
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coccidial and Mycoplasmal Infections on Carotenoid-Based Plumage Pigmentation in Male House Finches

Abstract: Carotenoid pigments produce the ornamental red, orange, and yellow integumentary coloration of many species of animals. Among individuals of a population, the hue and saturation of carotenoid-based ornaments can be extremely variable, and studies of fish and birds have shown that females generally prefer males that display the most saturated and reddest coloration. Consequently, there has been a great deal of interest in determining the proximate factors that affect individual expression of carotenoid-based pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
91
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(101 citation statements)
references
References 42 publications
8
91
1
1
Order By: Relevance
“…in review), yet contradictory to earlier studies that found high mortality in captive finches infected with Mycoplasma (Lutrell et al . 1998; Brawner et al . 2000).…”
Section: Discussionmentioning
confidence: 99%
“…in review), yet contradictory to earlier studies that found high mortality in captive finches infected with Mycoplasma (Lutrell et al . 1998; Brawner et al . 2000).…”
Section: Discussionmentioning
confidence: 99%
“…[40] in male house finches ( Haemorhous mexicanus ) at seven sites along a gradient of urbanization in the city of Phoenix, Arizona, USA. House finches are native residents of the desert southwestern United States but are now abundant inhabitants of cities around North America [41].…”
Section: Introductionmentioning
confidence: 99%
“…, 2000), such parasites should be especially suitable for the detection of mechanisms ensuring the honesty of signals. Indeed, the effect of experimental coccidian infection upon the carotenoid‐based ornaments has been detected in three cardueline finch species (Brawner et al. , 2000; McGraw & Hill, 2000; HĂ”rak et al.…”
Section: Introductionmentioning
confidence: 99%